Shoreline Change with Groin Coastal Protection Structure at North Java Beach - Oki Setyandito; Aldo Christanto Purnama; Nur Yuwono; Juliastuti Juliastuti; Yureana Wijayanti (Bina Nusantara University, 2020)
The research aimed to study the effect of groin application to erosion at the shoreline. The method utilized the bathymetry and topography data of north beach of Balongan, West Java. Modeling of the shoreline change due to groin installment used software called GENESIS. Based on analysis result, it is found that the significant wave direction comes from the southeast with significant wave height of 1,18 meters and surf zone width of 140 meters. It is concluded that at research area of north beach of west Java, I-groin with length of 70 meters and T head groin of 60 meters in long T-groin effectively overcome erosion and advance the coastline by 10786,62 m2 or in average 6,3 meters.